2008
DOI: 10.1242/dev.014829
|View full text |Cite
|
Sign up to set email alerts
|

Bud specific N-sulfation of heparan sulfate regulatesShp2-dependent FGF signaling during lacrimal gland induction

Abstract: Preferential outgrowth of the bud cells forms the basis of branching morphogenesis. Here, we show that lacrimal gland development requires specific modification of heparan sulfates by Ndst genes at the tip of the lacrimal gland bud. Systemic and conditional knockout experiments demonstrate the tissue specific requirement of Ndst1 and Ndst2 in the lacrimal gland epithelial, but not mesenchymal, cells, and the functional importance of Ndst1 in Fgf10-Fgfr2b, but not of Fgf1-Fgfr2b, complex formation. Consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
105
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 44 publications
10
105
1
Order By: Relevance
“…Similarly, we have shown in lens development that a lack of heparan sulfate N-sulfation disrupts its interaction with Fgf8b-Fgfr3c but not with the Fgf8b-Fgfr3b pair (28). We recently showed that N-sulfated heparan sulfate is highly enriched in the lacrimal gland bud, which potentiates a restricted activation of FGF signaling during lacrimal gland outgrowth (29). Taken together, these findings suggest that FGF signaling is sensitive to the positional distribution of sulfate groups in the heparan sulfate chains.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Similarly, we have shown in lens development that a lack of heparan sulfate N-sulfation disrupts its interaction with Fgf8b-Fgfr3c but not with the Fgf8b-Fgfr3b pair (28). We recently showed that N-sulfated heparan sulfate is highly enriched in the lacrimal gland bud, which potentiates a restricted activation of FGF signaling during lacrimal gland outgrowth (29). Taken together, these findings suggest that FGF signaling is sensitive to the positional distribution of sulfate groups in the heparan sulfate chains.…”
mentioning
confidence: 78%
“…Immunohistochemistry and RNA in Situ Hybridization-Immunohistochemistry was performed on cryosections or paraffin sections as previously described (28,29 A series of phage-display derived antibodies with VSV-tag were used to detect specific modifications of heparan sulfate in tissue sections (33). Cryo-sections were hydrated in PBS for 10 min, quenched of peroxidase activity by 3% H 2 O 2 and 10% methanol in PBS solution, and then blocked with 2% BSA in PBS at room temperature for 1 h followed by incubation with phage-display-derived antibodies (1:1-1:5 diluted with 0.2% BSA/PBS) at 4°C overnight.…”
Section: Mice-hs6st1mentioning
confidence: 99%
See 3 more Smart Citations